2014
DOI: 10.1089/tmj.2013.0329
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Health-Related Uses of Mobile Phones and Internet with Homeless Veterans: Results from a Multisite Survey

Abstract: These findings suggest new avenues for communication and health interventions for hard-to-reach homeless veterans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 17 publications
3
52
2
Order By: Relevance
“…13 In the current study in-depth interviews were conducted with 30 homeless veterans to 49 explore, access to, and perceptions of, information technologies; and, attitudes toward using 50 information technologies for health related purposes. …”
Section: Methodsmentioning
confidence: 99%
“…13 In the current study in-depth interviews were conducted with 30 homeless veterans to 49 explore, access to, and perceptions of, information technologies; and, attitudes toward using 50 information technologies for health related purposes. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, while the mean age of cell phone owners was higher than for those who did not own a cell phone, there were no differences in cell phone ownership by race, gender, or indicators of education. More recently, McInnes et al (2014) surveyed 106 homeless veterans utilizing healthcare services and not living on the streets and found that 89% had a cell phone. So, across studies of homeless people of different ages and homeless experiences, we find that between 44% of nonsheltered homeless to 89% of homeless veterans not living on the street owned cell phones.…”
mentioning
confidence: 99%
“…Further, she found that among her homeless sample, computer users were younger and more likely to have a high school diploma, but that there were no differences by gender or race (Eyrich-Garg, 2011). McInnes et al (2014) surveyed 106 homeless veterans utilizing healthcare services and not living on the streets and found that 76% used the internet. It would seem that, although lagging behind the general population, the number of homeless people using the internet is increasing and that younger and better educated homeless persons use computers more frequently than others.…”
mentioning
confidence: 99%
“…First, access to technology can assist with job acquisition, life-skills development, and health-related services, including diet and nutrition education [26,32,33]. These immediate and substantial benefits for shelter residents argue for ways to leverage technology-based interventions for health promotion.…”
Section: Opportunities For Interveningmentioning
confidence: 99%